2003
DOI: 10.1128/mcb.23.14.4959-4971.2003
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced Gene Expression Occurs Solely through the Action of Hypoxia-Inducible Factor 1α (HIF-1α): Role of Cytoplasmic Trapping of HIF-2α

Abstract: The hypoxia-inducible factors 1␣ (HIF-1␣) and 2␣ (HIF-2␣) have extensive structural homology and have been identified as key transcription factors responsible for gene expression in response to hypoxia. They play critical roles not only in normal development, but also in tumor progression. Here we report on the differential regulation of protein expression and transcriptional activity of HIF-1␣ and -2␣ by hypoxia in immortalized mouse embryo fibroblasts (MEFs). We show that oxygen-dependent protein degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
122
4
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(146 citation statements)
references
References 47 publications
18
122
4
2
Order By: Relevance
“…These cell lines were either only immortalized by SV40 large T (MEF-Hif1a -/-T) or immortalized and transformed by H-ras (MEF-Hif1a -/-r T), respectively (Feldser et al , 1999 ;Ryan et al , 2000 ). Importantly, these MEF cell lines were shown to lack functional HIF-2 α protein (Park et al , 2003 ). Confirming the results obtained with HEK293 cells, γ H2AX levels in wt MEFs accumulated after 24 h exposure to 0.2 % O 2 but were strongly impaired in MEFs devoid of HIF-1 α .…”
Section: Hypoxic γ H2ax Accumulation Is Hif Dependentsupporting
confidence: 73%
“…These cell lines were either only immortalized by SV40 large T (MEF-Hif1a -/-T) or immortalized and transformed by H-ras (MEF-Hif1a -/-r T), respectively (Feldser et al , 1999 ;Ryan et al , 2000 ). Importantly, these MEF cell lines were shown to lack functional HIF-2 α protein (Park et al , 2003 ). Confirming the results obtained with HEK293 cells, γ H2AX levels in wt MEFs accumulated after 24 h exposure to 0.2 % O 2 but were strongly impaired in MEFs devoid of HIF-1 α .…”
Section: Hypoxic γ H2ax Accumulation Is Hif Dependentsupporting
confidence: 73%
“…Previous work with non-RCC cells has indicated that although the large majority of hypoxia inducible genes are responsive to HIF-1a (Hu et al, 2003;Park et al, 2003;Sowter et al, 2003;Manalo et al, 2005;Wang et al, 2005), two distinct patterns of response are observed with some genes being exclusively responsive to HIF-1a and some responding to both HIF-1a and HIF-2a. In RCC cells, this transcriptional selectivity is more marked with the former group of genes remaining exclusively responsive to HIF-1a and the latter becoming dominantly, or even exclusively, responsive to HIF-2a (Sowter et al, 2003;Raval et al, 2005).…”
Section: Resultsmentioning
confidence: 98%
“…Although structurally highly similar, specific roles of HIF-a isoforms in tumorigenesis have been defined Semenza, 2010). Pioneering work using genetically modified mouse embryonic fibroblast with targeted disruption of both Hif1a alleles suggested a predominant role of HIF-1a for regulating gene expression in response to hypoxia (Park et al, 2003), a finding that was confirmed for a limited number of classical HIF target genes in human cell lines by using transient RNA interference against both HIF-a isoforms (Sowter et al, 2003). However, expression analyses in a renal clear cell carcinoma-derived cell line deficient for HIF-1a revealed preserved hypoxic induction of many known HIF target genes, indicating that effectively both HIF-a isoforms contribute to hypoxia-induced transcription (Hu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%